Delayed cerebral ischaemia in patients with aneurysmal subarachnoid haemorrhage: Functional outcome and long‐term mortality. Issue 9 (7th June 2019) - Olsen, Markus Harboe; Orre, Matias; Leisner, Anna Cold Winge; Rasmussen, Rune; Bache, Søren; Welling, Karen‐Lise; Eskesen, Vagn; Møller, Kirsten
Abstract : Introduction: Delayed cerebral ischaemia (DCI) is one of the most frequent complications of aneurysmal subarachnoid haemorrhage (aSAH). The purpose of the present retrospective cohort study of patients with aSAH was to identify the association between DCI, functional outcome and 4‐year mortality. Methods: Patients admitted to the Neurointensive Care Unit at Rigshospitalet, Copenhagen, with aSAH from 1 January 2010, through 31 December 2013 were registered. Patients were categorized into 3 groups: (a) those with DCI, defined as either a decline in consciousness or focal neurological deficits lasting ≥1 hour without any other detectable cause, (b) those without DCI, or (c) those who were unassessable for DCI. Functional neurological outcome after 6 months, as measured by the modified Rankin Scale (mRS), was dichotomized into good (mRS 0‐2) and poor (mRS 3‐6). Kaplan‐Meier survival curves were constructed, and incidence risk rates were calculated both to determine the association between DCI and mortality. Results: Four hundred ninety‐two cases of aSAH were recorded in the study period. DCI occurred in 23% of all patients, corresponding to 33% of assessable patients. Patients without DCI had the best functional outcome (mRS) compared to patients with DCI and patients who were unassessable; furthermore, the latter had worse outcomes than patients with DCI. Patients diagnosed with DCI had significantly higher mortality than those without DCI, even ignoring the first 14 days after admission. Conclusion: DCI may be associated with both short‐ and long‐term morbidity and mortality in patients with aSAH.